Model Intervensi Psikopedagogis Kolaboratif bagi anak usia dini berkebutuhan khusus: Studi lapangan di TKM NU Dewi Masithoh 1 Kalipare - Nurfaizah, Rosania (Maliki Interdisciplinary Journal, 2025)
This study aims to describe afamily- and school-based collaborative psychopedagogical intervention model foryoung children with special needs (ABK) in inclusive educational institutions. The studywas conducted qualitatively through observation, in-depth interviews, anddocumentation at TKM NU Dewi Masithoh 1 Kalipare. The results show thatinterventions in the form of structured activities such as sensory play, pattern games, music/murottal therapy, and simple communication exercises canimprove focus, emotional regulation, and interaction skills in children with ADHD,mild autism, and speech delay. The success of the intervention was influenced by close collaboration between teachers and parents, characterized by sharedperceptions, regular communication, and continuity of strategies between home andschool. These findings confirm that a family-school-based intervention approachcan be an effective model in inclusive early childhood education, especially when tailored to local characteristics and the specific needsof children. This study recommends strengthening the role of parents andthe capacity of teachers in designing and implementingcollaborative intervention programs on an ongoing basis.